Advertising : types, trends, and controversies - Mann, Evelyn P. (Advertising: Media, Marketing and Consumer Demands., 2012)
"In today's cluttered media environment, advertisers are constantly in search of new ways to improve the strength and effectiveness of their advertisements. They are continuously competing for the limited attention resources of consumers. In this book, the authors present current research in the study of the types and trends of new advertising techniques. Topics discussed include the lipdub as a trend in corporate communications; interactive digitial television (IDTV) advertising; differential effects of visual and verbal elements in advertisements for new brands and extensions; the internet as an important advertising medium and children and advertising."--Publisher.